A relação do bilinguismo com capacidades cognitivas : memória de trabalho, atenção, controle inibitório e processamento de discurso - Pereira, Lisiane Neri (2012)
Through an interaction between Linguistics and Neuropsychology, the present study has aimed to verify the influence of bilingualism on a higher effective processing of some cognitive components. This relation has been demonstrated in recent studies, although they have presented incipient results towards the effects of bilingualism on working memory, for example. Other investigations have suggested that the advantage of bilingualism on the controlling of executive functions, such as attention and inhibitory control, seems to happen at different ages, from childhood to adulthood and elderly. In this research, we have attempted to identify the presence of a relation between bilingualism and the performanceof cognitive abilities such as the ones measured in tasks of working memory, executive functions such as the attention factor and inhibitory control, cognitive flexibility and linguistic aspects observed in inferencial aspects. For this purpose, neuropsychological tests have been administered to two groups: a bilingual sample speaker of the Italian Venice dialect and Brazilian Portuguese, and to a monolingual sample constituted by speakers of Brazilian Portuguese. Both groups have been divided into elderly people from a range of 60 to 75 years old, and young adults from a range of 19 to 35 years old. To evaluate comprehension capacity and narrative production, a subtest of Protocole MEC in its Brasilian Portuguese version, has been applied. Inhibitory control was evaluated through Random Number Generation and N-Back tests, instruments also used within Auditive Sentence Word Span NEUPSILIN for working memory evaluation. A Mini-mental State Examination subtest has evaluated the attentional component. For a broader observation of executive control and cognitive flexibility, ithas been performed the crossing of attentional component and inhibitory control results. Significative results between the samples have occurred in variables of the Random Number Generation (GAN) task, in its subsets(correct scores 2 seconds pace, mistakes on direct sequencing 2 seconds pace, mistakes on indirect sequencing 2 seconds pace) and in subsets of the N-Back task (correct scores on N-back 3 A, Span on N-back 3 A). Data have suggested a positive influence of bilingualism on the performance of working memory central executive and inhibitory control, cognitive flexibility and selfmonitoring.